Haemoglobinopathies in Europe: health & migration policy perspectives - Aguilar Martinez, Patricia (BioMed Central, 2014)
BACKGROUND: Major haemoglobinopathies (MH), such as thalassaemia syndromes (Thal) and sickle cell disorders (SCD), are genetic defects associated with chronic anaemia and other complications. In Europe, MH are rare diseases (RD) but their prevalence is significantly growing in many countries due to mobility and migration flows. This creates a growing health problem in the EU that has not yet been effectively addressed by Member States (MS) authorities. The present study has been conducted with the aim of: (i) providing an overview of policies for MH in 10 EU member states (MS) (ii) analysing the challenges linked to these RD due to growing requirements imposed by population, mobility and migration trends and (iii) identifying gaps, proposing improvements on existing policies, or developing new ones to fit the identified needs. METHODS: The study has been undertaken by a group of members of the European Network for Rare and Congenital Anaemias (ENERCA) and the Thalassaemia International Federation (TIF), in collaboration with the public affairs firm Burson-Marsteller Brussels. Data from 10 EU countries have been gathered using targeted desk research and one-to-one interviews with local stakeholders, including healthcare professionals, patients and public health officers/providers. RESULTS: 1. MH are the most common RD in all the 10 countries, 2. Data on prevalence, overall burden, trends, and clinical follow up costs are lacking in most countries. 3. Neonatal screening practices show a wide variation across and within countries. 4. Awareness on MH and their related complications is very low, exception made of Italy, Greece, Cyprus and UK, 5. No disaggregated data is available to understand the impact of mobility and migration on the prevalence of haemoglobinopathies, and how healthcare delivery systems should adapt to respond to this situation. 6. Targeted policy measures and/or actions are generally lacking and/or delayed. CONCLUSIONS: Ten policy recommendations have been drawn from this study, building on 2006 WHO recommendations for MH to include haemoglobinopathies in National Plans of Actions for Rare Diseases.